2011
DOI: 10.1108/17466661111190956
|View full text |Cite
|
Sign up to set email alerts
|

Parents seeking help in child rearing: who are they and how do their children behave?

Abstract: PurposeThe main aim of this study is to explore characteristics of parents who signed up for parenting classes offered to the universal population and their reasons for participation.Design/methodology/approachData were obtained from parents in a study on parent training for children aged two to eight years (n=189), and a follow up survey on these parents (n=118).FindingsParents had high education, were married, and employed in full time jobs. The mean age of the children was under four years, and their Intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…This represents a medium difference according to Cohen’s criteria, and the children in our sample had significantly higher scores on the ECBI Intensity scale than the norm for their age groups (Reedtz et al ., 2008). Some 35% of the parents also reported parental concern for their child’s behavior as an important reason for participating in the study (Reedtz et al ., 2010). As the sample in the present study had elevated ECBI scores compared to the norm there was a significant potential for improvement among the few children with the highest scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents a medium difference according to Cohen’s criteria, and the children in our sample had significantly higher scores on the ECBI Intensity scale than the norm for their age groups (Reedtz et al ., 2008). Some 35% of the parents also reported parental concern for their child’s behavior as an important reason for participating in the study (Reedtz et al ., 2010). As the sample in the present study had elevated ECBI scores compared to the norm there was a significant potential for improvement among the few children with the highest scores.…”
Section: Discussionmentioning
confidence: 99%
“…Parents in this sample worked full time (61%), were two‐parent families (80%), and were educated to bachelor level or higher (78%) (Reedtz, Martinussen, Jørgensen, Handegård & Mørch, 2010). The mean age of the children was less than four years, and their Intensity scores on ECBI were higher than the Norwegian mean scores for their age group (Reedtz, Bertelsen, Lurie, Handegård, Clifford & Mørch, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, how families view behavior problems symptoms and react upon them may be otther socially graded asset that influence service utilization. The social gradient found in other studies of service utilization, particularly the Norwegian study by Reedtz et al, (2011) where they found social gradients in a universally provided evidence-based parent training program, may suggest that the mechanisms and social processes associated with high amounts of flexible assets come less into play in selected intervention where provision is based on professional judgments.…”
Section: Discussionmentioning
confidence: 87%
“…However, others have pointed out that the social gradient in parent training outcomes are somewhat mixed . Second, several scholars have documented social gradients in utilization of evidencebased treatments for behavior problems, meaning that children from low-resource backgrounds are less likely to utilize help services (Bussing, Zima, Gary, & Garvan, 2003;Haggerty et al, 2002;Kazdin, Holland, & Crowley, 1997;Pettersson, Lindén-Boström, & Eriksson, 2009;Reedtz, Martinussen, Jørgensen, Handegård, & Mørch, 2011). Taken together, if there are social disparities in both service utilization and the treatment outcomes of evidence-based parent training interventions, the effectiveness of the interventions and adequacy of service provision would be compromised.…”
Section: Social Disparities In Service Utilization and Outcomes In Trmentioning
confidence: 99%
“…The study population is generally representative of families in the city, region and country where it was conducted [34]. Most families in this sample had mothers working full time (61 %) and were two-parent families (80 %) with one or two children (79 %).…”
Section: Methodsmentioning
confidence: 99%